Antenatal group-based psychoeducation to improve postpartum depression literacy in primary health care institutions in Ethiopia: a cluster randomized controlled trial - Tessema, Marta; Abera, Muluemebet; Birhanu, Zewdie (Frontiers in Psychiatry, 2025)
BackgroundPostpartum depression literacy assists mothers in recognizing and preventing postpartum depression (PPD). So, this study assessed the effectiveness of antenatal group psychoeducation in improving PPD literacy among pregnant women in Jimma, Ethiopia.MethodsA cluster randomized controlled trial was conducted from 28 March to 1 December 2022 involving 32 non-adjusted health centers that were randomized into two groups (16 health centers for each arm). The study enrolled 550 participants who scored (0–9) on the Patient Health Questionnaire-9. The intervention group received standard antenatal care and group psychoeducation, while the control group received only standard care. Postpartum depression literacy was assessed in face-to-face interviews at 12–20 weeks gestation and 6 weeks postpartum using the PPD literacy scale. Higher scores indicated higher literacy. An intention-to-treat analysis was used. Demographic factors were compared between groups using χ² and independent sample t-tests, indicating no significant differences except for educational status and parity. General linear models and mixed-effect models assessed intervention effects and outcome variable predictors, respectively.ResultsThe overall response rate was 92.9%. The study demonstrated a significant difference between groups regarding the overall mean PPD literacy score (intervention, 3.75 ± 0.46; control, 3.48 ± 0.46; ηp² = 0.07), ability to recognize PPD (intervention, 4.30 ± 0.64; control, 3.94 ± 0.75; ηp² = 0.06), knowledge of risk factors and causes (intervention, 4.03 ± 0.69; control, 3.67 ± 0.70; ηp² = 0.05), and access to PPD information (intervention, 3.28 ± 1.25; control, 2.01 ± 1.13; ηp ²= 0.21) at p = 0.001, with marginal significance regarding self-care activities (intervention 4.37 ± 0.54, control 4.26 ± 0.50, ηp² = 0.01, p = 0.051). Conversely, there were no significant differences in knowledge of professional help (intervention 2.97 ± 1.13, control 2.83 ± 0.80, p² = 0.00, p = 0.303), beliefs regarding professional help (intervention 2.67 ± 0.89, control 2.50 ± 0.72, p² = 0.01, p = 0.063), and attitudes toward PPD recognition and help seeking (intervention 3.91 ± 1.02, control 3.91 ± 1.02, p² = 0.00, p = 0.586). Moreover, partner emotional support (AOR = 0.1, 95% CI = 0.02–0.17), maladaptive coping [AOR = −0.14, 95% CI = −0.22–(−0.07)], and multiparty [AOR = −0.15, 95% CI = −0.22–(−0.08)] showed significant associations with overall PPD literacy score.ConclusionsThe study showed that antenatal group psychoeducation had a moderate effect on overall PPD literacy score. However, further research is required to effectively change negative attitudes toward seeking formal help.Clinical Trial Registrationhttps://pactr.samrc.ac.za/, identifier PACTR 202203616584913.